Adenomatous residue in cancerous papilla of Vater. Issue 12 (December 1981) - Kozuka, S; Tsubone, M; Yamaguchi, A; Hachisuka, K
Abstract : Surgical specimens of carcinoma in the papilla of Vater were studied histologically. Adenomatous residue which suggested that the carcinoma was derived from a pre-existing adenoma was found in 18 cases (81.8%) out of 22. The histological transition of adenoma into carcinoma was also frequently seen.